First-Principles Calculation of Physical Tensors of α-Diisopropylammonium Bromide (α-DIPAB) Molecular Ferroelectric Crystal - Alsaad, Ahmad; Al-Aqtash, Nabil; Sabirianov, Renat F.; Ahmad, Ahmad; Al-Bataineh, Qais M.; Qattan, Issam; Albataineh, Zaid (Frontiers in Physics, 2019)
We report accurate calculations of tonsorial elements of α-Diisopropylammonium bromide (α-DIPAB) molecular ferroelectric crystal. In particular, elastic, piezoelectric and dielectric tensors were calculated using Vienna ab initio simulation package (VASP) within the framework of density functional (DFT) theory. The determination of above parameters allows an accurate description of the energy landscape for modeling of realistic devices at finite temperatures. We determine the major physical tensors in energy expansion of total energy per volume of un-deformed crystal to provide experimentalists with valuable information for designing and fabrication of pyroelectric detectors, capacitors, piezoelectric ferroelectric memories, display devices, electro-optic devices, and ultrasound transducers based on α-DIPAB. The spontaneous polarization P_s was calculated using Berry phase approach and found to be 22.64 μC⁄〖cm〗^2 in agreement with reported theoretical value. The dynamical Born effective charge tensor is reported for all atoms in the unit cell of α-DIPAB to get a deeper insight into the bonding network. The neighboring layers of DIPA molecules were found to be strongly crenelated due to the strong short-ranged electrostatic repulsion between Br sites in the DIPAB crystal structure. The organization of species in DIPA molecular layer as well as in the bromine “stitching” layer is essential for accurate calculation of DIPAB elastic properties. Having understood the actual network bonding in α-DIPAB, we calculated the components of the elastic moduli tensor. Our results indicate that a Young’s modulus of 10-180 GPa and a shear modulus of 4-26 GPa were found. Thus, α-DIPAB phase has a great potential to be a terrific candidate for flexible electronic device applications. The value of the principle component of electronic contribution to the static dielectric tensor of α-DIPAB is found to be ≈ 2.5, i.e. 50% smaller than that in typical perovskite-based ferroelectrics. Therefore, α-DIPAB is anticipated to exhibit creative materials' innovations. It offers highly customized features for specific applications, including insulation on polymer thick film conductive inks in the manufacture of membrane switches and flex circuits. Furthermore, clamped-ion piezoelectric tensor is calculated. Our results indicate a reasonable piezoelectric response of this polar crystal making it a low cost attractive candidate for piezoelectric applications.